Ceramide Accumulation Is Associated with Declining Verbal Memory in Coronary Artery Disease Patients: An Observational Study. - Chan, Parco; Saleem, Mahwesh; Herrmann, Nathan; Mielke, Michelle M; Haughey, Norman J; Oh, Paul I; Kiss, Alexander; Lanctôt, Krista L (J Alzheimers Dis, 2018)
BACKGROUND: Biomarkers in cognitively vulnerable populations, like those with coronary artery disease (CAD), may inform earlier intervention in vascular neurodegeneration. Circulating ceramide C18:0 (CerC18:0) is associated with changes in verbal memory in early neurodegeneration and CAD progression. OBJECTIVE: To investigate whether plasma CerC18:0 accumulation is associated with longitudinal declines in verbal memory performance in CAD. METHODS: In addition to total CerC18:0, we assessed its relative abundance to its precursors as ratios: CerC18:0 to monohexosylceramide C18:0 (MHxCer18:0), CerC18:0 to sphingomyelin C18:0 (SM18:0), and CerC18:0 to sphingosine-1-phosphate (S1P). Verbal memory was assessed using the California Verbal Learning Test 2nd Ed. Using mixed models in 60 CAD participants, we evaluated associations between baseline CerC18:0 ratios and changes in verbal memory performance, adjusting for age, body mass index, and education. Given that cognitive decline is more rapid following onset of deficits, these associations were compared between those with possible mild vascular neurocognitive disorder (MVND). RESULTS: Increased baseline CerC18:0 concentrations correlated with worse verbal memory performance over time (b[SE] = - 0.91[0.30], p = 0.003). Increased baseline CerC18:0/SM18:0 (b[SE] = - 1.11[`], p = 0.03) were associated with worse verbal memory performance over time. These associations were not mediated by whether or not patients had possible MVND at baseline. CONCLUSION: These findings support aberrant CerC18:0 metabolism as an early neurobiological change in vascular neurodegeneration. Future studies should measure enzymes responsible for conversion of sphingolipid precursors into CerC18:0 to assess enzymatic activity.

Antihypertensive Treatment is associated with MRI-Derived Markers of Neurodegeneration and Impaired Cognition: A Propensity-Weighted Cohort Study. - Edwards, Jodi D; Ramirez, Joel; Callahan, Brandy L; Tobe, Sheldon W; Oh, Paul; Berezuk, Courtney; Lanctôt, Krista; Swardfager, Walter; Nestor, Sean; Kiss, Alexander; Strother, Stephen; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension is an important risk factor for Alzheimer's disease (AD) and cerebral small vessel disease. Angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are common anti-hypertensive treatments, but have differential effects on cortical amyloid. OBJECTIVE: The objective of this study was to evaluate associations between anti-hypertensive treatment, brain volume, and cognition, using a propensity-weighted analysis to account for confounding by indication. METHODS: We identified a cohort of normal elderly adults and individuals with mild cognitive impairment (MCI) or AD (N = 886; mean age = 75.0) from the Alzheimer's Disease Neuroimaging Initiative. Primary outcomes were brain parenchymal fraction, total hippocampal volume, and white matter hyperintensity (WMH) volume. Secondary outcomes were standardized scores on neuropsychological tests. Propensity-weighted adjusted multivariate linear regression was used to estimate associations between anti-hypertensive treatment class and MRI volumes and cognition. RESULTS: Individuals treated with ARBs showed larger hippocampal volumes (R2 = 0.83, p = 0.05) and brain parenchymal fraction (R2 = 0.83, p = 0.01) than those treated with ACEIs. When stratified by diagnosis, this effect remained only in normal elderly adults and MCI patients, and a significant association between ARBs and lower WMH volume (R2 = 0.83, p = 0.03) emerged for AD patients only. ARBs were also associated with significantly better performance on tests of episodic and verbal memory, language, and executive function (all p < 0.05). CONCLUSIONS: Findings are consistent with evidence for a neuroprotective effect of treatment with ARBs for brain structure and cognition. This study has potential implications for the treatment of hypertension, particularly in elderly adults at risk of cognitive decline and AD.